Pengaruh Rasio Likuiditas, Leverage Dan Profitabilitas Terhadap Nilai Perusahaan Pada Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2012 - Siska Adelina; Restu Agusti; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Value of the company can deliver maximum shareholder wealth if the stock price increases. The higher the stock price of a company, the higher shareholder wealth. Value of the company is a reflection of the addition of a number of companies with debt equity firm. There are several factors that affect the value of the company, some of which are liquidity ratios, leverage and profitability. The purpose of this study was to determine the effect Liquidity Ratio, Leverage and Profitability on Firm Value.The results of this study are as follows: 1) There is no influence of variables liquidity (current ratio) of the value of the company; 2) There is no influence of variables Leverage (Debt to Equity Ratio) of the value of the company; 3) There is the influence of variable Profitability (Return on Equity) of the value of the company; 4) As much as 31.5% variation in the dependent variable, Tobins Q (enterprise value), can be explained by the variation of the three independent variables are the Current Ratio, Debt to Equity Ratio, and Return on Equity, while the remaining 68.5% is influenced by other factors not be included in the regression model.Keywords: Current Ratio, Debt to Equity Ratio, Return on Equity, and Tobins Q